2016
DOI: 10.1002/joc.4939
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variation of tropical cyclone genesis and its relationship to the monsoon trough over the western North Pacific

Abstract: Using the European Centre for Medium‐Range Weather Forecasts Interim Reanalysis data set and the tropical cyclone (TC) best track data obtained from the International Best Tracks Archive for Climate Stewardship project from June to November for the epoch of 1979–2013, this study reexamines the recent interdecadal shift in TC genesis over the western North Pacific (WNP) in the late 1990s. An interdecadal decrease in the frequency of the WNP TC genesis was observed during 1998–2013 compared to the period of 1979… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
(60 reference statements)
5
52
0
Order By: Relevance
“…3c, d, green bars), re-confirming that more and more TCs form over the northwestern WNP since 1998 (Fig. A3) from another angle, which is consistent with previous studies (e.g., Hsu et al 2014;Choi et al 2015Choi et al , 2017He et al 2015;Hong et al 2016;Zhao and Wang 2016;Huangfu et al 2017).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…3c, d, green bars), re-confirming that more and more TCs form over the northwestern WNP since 1998 (Fig. A3) from another angle, which is consistent with previous studies (e.g., Hsu et al 2014;Choi et al 2015Choi et al , 2017He et al 2015;Hong et al 2016;Zhao and Wang 2016;Huangfu et al 2017).…”
Section: Resultssupporting
confidence: 91%
“…It was ever pointed out that the mean TCL showed a westward shift over the WNP mainly due to (1) the pronounced westward shift of TUTT (Wu et al 2015) and/or (2) the interdecadal change of the WNP MT (Huangfu et al 2017). On the other hand, Zhang et al (2014) demonstrated that southern China had experienced increasing autumn drought due to the ENSO regime shift in the past decades.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations